1999
DOI: 10.1074/jbc.274.17.11977
|View full text |Cite
|
Sign up to set email alerts
|

Intra-M Phase-promoting Factor Phosphorylation of Cyclin B at the Prophase/Metaphase Transition

Abstract: in vivo phosphorylation as shown by phosphopeptide maps of in vivo and in vitro phosphorylated cyclin B. We demonstrate that Cdc2 itself is the cyclin B kinase; cyclin B phosphorylation requires Cdc2 activity both in vivo (sensitivity to vitamin K 3 , a Cdc25 inhibitor) and in vitro (copurification with Cdc2-cyclin B, requirement of Cdc2 dephosphorylation, and sensitivity to chemical inhibitors of cyclin-dependent kinases). Furthermore, cyclin B phosphorylation occurs as an intra-M phase-promoting factor react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 48 publications
3
48
1
Order By: Relevance
“…The location of the initial entry suggests that the first molecules to be phosphorylated are near the centrosomes. In starfish, cyclin B may be phosphorylated by an intermolecular action of Cdc2-cyclin B (Borgne et al, 1999). Our observation of entry of cyclin B-GFP suggests that activation of Cdc2-cyclin B first occurs in the region of the centrosomes.…”
Section: Accumulation In the Nucleusmentioning
confidence: 78%
“…The location of the initial entry suggests that the first molecules to be phosphorylated are near the centrosomes. In starfish, cyclin B may be phosphorylated by an intermolecular action of Cdc2-cyclin B (Borgne et al, 1999). Our observation of entry of cyclin B-GFP suggests that activation of Cdc2-cyclin B first occurs in the region of the centrosomes.…”
Section: Accumulation In the Nucleusmentioning
confidence: 78%
“…Because our extracts were made at a time corresponding to the beginning of mitosis, most CyclinB is nonphosphorylated and present in the inactive pre-MPF complex, containing inactive phosphorylated Cdc2. CyclinB is intraphosphorylated by activated Cdc2/CyclinB (Borgne et al, 1999) and the appearance of the upper form of CyclinB2 has been shown to strictly correlate with GVBD/metaphase in maturing Xenopus oocytes (Kobayashi et al, 1991). The appearance of the phosphorylated (upper) form can be considered to be a marker of MPF activation.…”
Section: Compartmentalisation Of Active and Inactive Cdc25c And Mpfmentioning
confidence: 99%
“…In addition, cyclin B1 is regulated by phosphorylation during G2 phase. Specifically, the cytoplasmic retention signal (CRS) domain of cyclin B1 is phosphorylated on four Ser residues, resulting in nuclear localization of MPF and access to critical nuclear substrates for G2-M progression (Li et al, 1995(Li et al, , 1997Borgne et al, 1999;Hagting et al, 1999).…”
Section: Introductionmentioning
confidence: 99%